Tendências e projeção da mortalidade do município de São Paulo - 1920 a 2100 - Flavia Sommerlatte Silva (2009)
The main goal of this master's thesis is to forecast mortality levels in São Paulo from 2006 to 2100, using the Lee-Carter model and the Lee-Miller variation, and applied the estimates to compute life-time annuities comparing scenarios using period and pseudo-cohort life-tables. We first tested the model by projecting life expectancy and mortality schedules for 2000 and compared with observed values. The fit of the model was good, and the observed value for 2000 fell into the confidence interval estimated by the forecast. The forecast results, by sex, were similar to what is observed in developed countries. The results for females showed better fit while the results for males were distorted by the increase in adult mortality observed in the 1980s and 1990s in São Paulo. In order to test and adjust the result, we tested two different methods: (1) consider that the male mortality of São Paulo, during the period of 1980 to 2005, was the forecasted mortality, fitted using data from 1920 to 1980; (2) consider that the deaths due to violent causes, during the same period, occurred because of all other causes of death. The results for the second method fitted the model better than the first one. We then applied the forecasted values to estimate life-time annuities comparing a period life-table to a pseudo-cohort one. We find that the estimated values incorporating mortality changes were much higher than when we used the 2005 period life-table.